2016
DOI: 10.1016/j.eiar.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Environmental Assessment practices in European small islands: Insights from Azores and Orkney islands

Abstract: The literature concerning Strategic Environmental Assessment (SEA) often refers to the importance of context-specific approaches. However, there is a lack of systematised and consistent studies that enhance tailor-made SEA practices and procedures. Small islands are bounded units of study which may help explore SEA theory and practice in special territories. Small islands present particular features and unique values, such as, small size and population, geographic isolation, limited resources and vulnerable ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Azores economy depends highly on the public sector, but also on traditional sectors, where livestock production and the related industries have a paramount importance (Polido et al 2016). However, due to the vulnerability conditions of all small islands (i.e., small size, geographic isolation, narrow economic base, limited resources, ecosystem vulnerability to external ecological influences, relatively small population, with limited skills base), national and EU structural funds are central to the development of the region (Polido et al 2016).…”
Section: Azores Milk Production In the Framework Of The Portuguese Damentioning
confidence: 99%
See 1 more Smart Citation
“…Azores economy depends highly on the public sector, but also on traditional sectors, where livestock production and the related industries have a paramount importance (Polido et al 2016). However, due to the vulnerability conditions of all small islands (i.e., small size, geographic isolation, narrow economic base, limited resources, ecosystem vulnerability to external ecological influences, relatively small population, with limited skills base), national and EU structural funds are central to the development of the region (Polido et al 2016).…”
Section: Azores Milk Production In the Framework Of The Portuguese Damentioning
confidence: 99%
“…The Azores Islands (or Autonomous Region of the Azores) is a Portuguese autonomous region, with its own politicaladministrative status and government bodies (Polido et al 2016). The archipelago is composed by nine volcanic islands located in the center of the North Atlantic Ocean, approximately 1500 km from Lisbon and 3900 km from New York City (Ng et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although small islands (Kelman et al, 2015), and are vulnerable to climate change and sea-level rise, previous research showed that biodiversity, as well as climate change and sea-level rise, are sparsely addressed in the scientific literature concerning small islands (Polido et al, 2014). Furthermore, Polido et al (2016), while analysing SEA reports from the Azores (Portugal) and Orkney (Scotland), found that the assessment sistently addressed. It is noted T to Polido et al (2014), scored 12 out of 16 selections.…”
Section: Exploring Views and Perspectives Of European Small Islands Smentioning
confidence: 99%
“…In addition, as highlighted by respondents, there is the possibility th on the SEA team. Though this could occur where the SEA system relies on consultants to develop the SEA process, as is the Portuguese case identified by Polido et al (2016), if the SEA is mainly developed by in-house practitioners, as observed by McLauchlan and João (2012) for the Scottish case, probably these practitioners may perceive the Nonetheless, the majority of the respondents stated that to have trained staff on SEA and sustainability-related issues is important in small islands, as suggested by Bass and Dalal-Clayton (1995) and Ramos et al (2009).…”
Section: Exploring Views and Perspectives Of European Small Islands Smentioning
confidence: 99%
See 1 more Smart Citation